Effects on the survival rates, hematological parameters, and neurotransmitters in olive flounders, Paralichthys olivaceus, reared in bio-floc and seawater by Streptococcus iniae challenge. Issue 113 (June 2021) - Kim, Jun-Hwan; Sohn, Saebom; Kim, Su Kyoung; Kim, Seok-Ryel; Kim, Su-Kyoung; Kim, Su Mi; Kim, Na Young; Hur, Young Baek
Abstract: Bacterial infections cause huge losses to aquaculture globally, and increased antibiotic resistance means that alternative methods of reducing mortality from bacterial diseases are required. We compared the resistance of Juvenile olive flounders, Paralichthys olivaceus, to Streptococcus iniae between those reared in biofloc and seawater conditions for ten months. Experimental fish were challenged with S. iniae at concentrations of 0, 3.36 × 10 6, 3.36 × 10 7, 3.36 × 10 8, and 3.36 × 10 9 colony forming units (CFU)/g fish for 96 h to evaluate the difference in S. iniae susceptibility of flounders reared in biofloc and seawater. The 96 h lethal concentration 50% (LC50 ) of fish injected with S. iniae was 2.41 × 10 9  CFU/g fish in biofloc and 1.51 × 10 8  CFU/g fish in seawater. Hematological parameters such as hemoglobin and hematocrit significantly decreased when fish were challenged by S. iniae . Plasma components such as calcium, glucose, cholesterol, total protein, GOT, GPT, and ALP were significantly altered by S. iniae infection and acetylcholinesterase activity was significantly inhibited. These results indicate that S. iniae infection affects the survival rates, hematological parameters, and neurotransmitter levels of flounders reared in biofloc and seawater, and that S. iniae susceptibility was higher in flounders reared in seawater than those reared in biofloc. Graphical abstract: Image 1 Highlights: The 96 h LC50 was 2.41 × 10 9  CFU/g in bio-floc and 1.51 × 10 8  CFU/g in seawater. Hematological parameters and AChE were significantly changed when challenged by S. iniae. The susceptibility to S. iniae were more prominent in the flounders raised in seawater.